2020
DOI: 10.36877/aafrj.a0000150
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato Peel Flour Applications in The Textural Quality of Waffle Ice Cream Cone and Other Food Products

Abstract: Sweet potatoes are nutritious vegetables commonly grown in Malaysia. However, its beneficial skins are mostly peeled and thrown away. The sweet potato peel has a slightly bitter taste with its good nutritional food value in producing healthy food products. In this study, sweet potato peel flour (SPPF) is added to the existing wheat flour in the formulation of ice cream waffle cones. The amount of wheat flour added in the mixture depends on the SPPF amount added. Preliminary study on the content of protein, moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…SPP might have protein contents ranging from 0.80 to 13.80 g/100 g dry materials (DM) (Table 1). A study reported the protein content of 13.80 g/100 g orange‐fleshed SPP DM (Dom et al., 2020). Another study showed the protein content of 8.66 g/100 g purple‐fleshed SPP DM (Shaari et al., 2021).…”
Section: Nutritional Profiles Of Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…SPP might have protein contents ranging from 0.80 to 13.80 g/100 g dry materials (DM) (Table 1). A study reported the protein content of 13.80 g/100 g orange‐fleshed SPP DM (Dom et al., 2020). Another study showed the protein content of 8.66 g/100 g purple‐fleshed SPP DM (Shaari et al., 2021).…”
Section: Nutritional Profiles Of Sppmentioning
confidence: 99%
“…The peels of the purple‐fleshed variety might present lower lipid contents than their counterparts of the orange‐fleshed variety. The purple‐fleshed SPPs were reported a lipid content of 0.37 g/100 g DM (Shaari et al., 2021), compared with 13.5 g/100 g DM determined in the orange‐fleshed SPP (Dom et al., 2020). However, in recent years, there has been no study reporting the fatty acid profile of SPP.…”
Section: Nutritional Profiles Of Sppmentioning
confidence: 99%
See 1 more Smart Citation